Educational services, current framework - José María Vera Mur (ADIDE Federación, 2014)
The article aims to analyze and justify educational services, as instruments of support and supplement the regular educational performance. The conceptual framework of educational services as such, its character as an instrument and source of support and supplement the regular educational performance is analyzed, concluding with the different types according to the relevant education authorities. It is complemented with legal and regulatory references given in the regulatory provisions in force at both national and regional level. And also the situation in the next European environment (France).